2017
DOI: 10.5005/jp-journals-10024-2050
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis Knowledge and Related Health Behavior among Women in Jazan Region, Kingdom of Saudi Arabia

Abstract: Introduction: Osteoporosis is a systemic bone disease that can be prevented to some extent by awareness of its risk factors and related health behavior. The aim of this study was to collect information about knowledge and awareness of osteoporosis among women living in Jazan and to describe the type of food habits, sociodemographic characteristics, and other osteoporosis-related health behavior. Materials and methods:Self-administered questionnaires were used for data collection. The total participants were 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
3
0
3
Order By: Relevance
“…This finding is consistent with the studies from the central and southern provinces of Saudi Arabia. [ 2 22 ] Some authors from Saudi Arabia demonstrated lower levels of awareness of the disease among middle-aged and older women. [ 23 ] This disparity in osteoporosis awareness could be attributed to the sampling characteristics and study design.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the studies from the central and southern provinces of Saudi Arabia. [ 2 22 ] Some authors from Saudi Arabia demonstrated lower levels of awareness of the disease among middle-aged and older women. [ 23 ] This disparity in osteoporosis awareness could be attributed to the sampling characteristics and study design.…”
Section: Discussionmentioning
confidence: 99%
“…A legmagasabb pontszámot az egyetemi diplomával, továbbá a tudományos fokozattal rendelkező alanyok érték el. Korábbi vizsgálatok igazolták, hogy az osteoporosisban érintett nők tudása szignifikánsan nagyobb az osteoporosisban nem érintett nőkével összevetve [20,37]. Ez a mi vizsgálatunkban szintén megmutatkozott, mivel az osteoporosisban érintett résztvevők pontszáma (10,08 ± 8,82) magasabb volt, mint a csontritkulásban nem érintett résztvevőké (9,39 ± 6,67).…”
Section: Eredményekunclassified
“…In Jazan, Darout et al (36) reported that approximately 54% of non-healthcare workers and 62% of healthcare workers had adequate and good knowledge and awareness levels of osteoporosis, respectively. The authors also reported that more than half of their population were aware of the preventive dietary regimens, while approximately 48% and 44% of the healthcare and non-healthcare workers had inadequate knowledge of behavior and attitude of osteoporosis, respectively.…”
Section: Journal Of Healthcare Sciencesmentioning
confidence: 99%